Assessment of patient's satisfaction visiting a tertiary health care institute in north India - Madhur Verma; Kirtan Rana; Ankita Kankaria; Ramnika Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Background: Patient satisfaction is pertinent for measuring the performance of health-care service delivery, which is a multidimensional construct that depends on many factors. The main objective of this study was to assess the satisfaction of patients visiting a tertiary care hospital in Haryana. Materials and Methods: A cross-sectional study was conducted among patients visiting the outpatient department (OPD) and inpatient department (IPD) of the hospital from January to March 2019. Exit interviews were conducted using a structured questionnaire among patients visiting the OPD or IPD. The patient satisfaction was assessed based on four domains, namely registration process and experience before meeting the doctor, interaction with the doctor, hospital infrastructure, and medicine availability. The responses were captured on a Likert scale from one to five, and the scores were used to calculate the overall satisfaction. Results: Overall 84% of the patients were satisfied with the OPD services, whereas 77% of the patients were satisfied with the inpatient services. Male (odds ratio [OR] = 2.08; 95% confidence interval [CI]: 1.04-4.14) and literate patients (OR = 2.77; 95% CI: 1.4-4.14) had higher chances of being satisfied with the OPD services. Whereas students, retired and unemployed patients (OR = 4.67; 95% CI: 1.46-14.6), and those from a reserved social caste (OR = 3.38; 95% CI: 1.58-7.21) were more satisfied with the IPD services. Conclusion: This study suggests that patients were satisfied to a larger extent with both OPD and IPD services. Therefore, effective strategies should be in place to maintain high satisfaction among patients, and the institutes should strive to provide 100% satisfaction.